Effect of Al3+ on the spectroscopic properties of Eu2+- and Tb3+-Doped high silica glass. Issue 13 (1st July 2021) - Tao, Yiting; Yan, Sasa; Du, Ying; Wang, Panting; Chen, Danping
Abstract: In this study, Eu 2+ /Al 3+ -, Eu 2+ /Tb 3+ -, and Eu 2+ /Tb 3+ /Al 3+ -doped high silica glasses were prepared, and the effect of Al 3+ on the spectroscopic properties of Eu 2+ and Tb 3+ and the energy transfer of Eu 2+ →Tb 3+ was investigated. The results revealed that the addition of Al 3+ increased the luminescent intensity of the Eu 2+ -doped glass by approximately 400 times. An obvious Eu 2+ →Tb 3+ energy transfer occurred in the Eu 2+ /Tb 3+ -doped high silica glass, whose transfer efficiency can reached 66.9%. However, the efficiency continuously decreased as the Al 3+ concentration increased, and eventually, it dropped to 7.2%. These phenomena can be explained by the following: Al 3+ not only disperses Eu 2+ but also changes the field strength and symmetry of its neighboring environment, thus increasing its emission intensity. Moreover, Al 3+ destroys the strong dipole–dipole interactions between Eu 2+ and Tb 3+ in high silica glass due to its dispersive ability, which inhibits the energy transfer of Eu 2+ →Tb 3+ . This indicates that a small amount of Al 3+ can significantly modify the neighboring environment of Eu 2+ and change its light-emitting characteristics, potentially yielding efficient blue and green phosphors excited by near-ultraviolet light for use in white light-emitting diodes.